OPTIMIZATION OF PUMP MAINTENANCE TIME IN THE STEAM SYSTEM AREA PT XYZ USING A RELIABILITY AND MAINTENANCE VALUE STREAM MAPPING APPROACH - Pratama, Deden Yuda; Sulaiman, Mochamad; Hertadi, Christopher Davito Prabandewa (Journal of Industrial Engineering Management, 2024)
The pumps in Steam System PT XYZ frequently fail, resulting in a cumulative downtime of 15000 hours and potentially affecting output. The goal of this study is to examine the problem by 1) knowing the pump reliability, 2) evaluating the pump maintenance system using MVSM, and 3) offering recommendations based on the reliability and MVSM results in the Steam System Area of PT XYZ. The reliability values of pumps G04-III-A, G04-I-S, G04-I-A, G07-A, and G02-S were calculated as 52,20%, 45,59%, 50,19%, 47,09%, and 43,15%, respectively. The maintenance system was then evaluated using MVSM, yielding a Current State Map with a maintenance efficiency of 51%, a VA activity time of 8927 minutes, and an NVA activity time of 9672 minutes. The Future State Diagram The advice resulted in a 99% gain in maintenance efficiency, and NVA activity time was reduced by 9600 minutes. Maintenance time intervals on pumps G02-S, G04-I-A, G04-III-A, G04-I-S, and G07-A are recommended every 49 days, 31 days, 44 days, 35 days, and 76 days, respectively, while recommendations with the MVSM approach are in the form of eliminating the time delay that occurs when the material is not available, which is done by estimating the time the material is needed and the previous purchase time. This study concludes that by following the recommendations, the pump maintenance system in the Steam System Area of PT XYZ may be optimized.